Laser titanium non-stick cookware and method of making

CN117461986BActive Publication Date: 2026-10-23GUANGDONG MASTER GROUP +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311044851.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2026-10-23
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

[0006]但该技术所用底层材料存在耐高温性差、硬度低等问题,无法达到较好的使用效果

Benefits of technology

[0023]本发明的一种激光钛不粘锅具,通过多层依次交替叠加设置的纳米复合金属陶瓷层和纳米硅酸盐复合陶瓷层,可提供超硬、耐高温、不粘持久的涂层,为涂覆有该涂层的锅具赋予了优异的不沾性,超高硬度和耐磨性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117461986B_ABST
    Figure CN117461986B_ABST
Patent Text Reader

Abstract

The application discloses a laser titanium non-stick cookware, a multi-element and multi-layer nanometer titanium-based composite cermet coating is prepared on the inner surface of the cookware base by laser thermal spraying, the multi-element and multi-layer nanometer titanium-based composite cermet coating is composed of nanometer composite cermet and nanometer silicate composite ceramic which are alternately stacked and combined, and a superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cookware, and more particularly to a laser-coated titanium non-stick cookware and its preparation method. Background Technology

[0002] The main materials currently used for non-stick coatings on cookware include fluorinated coatings and ceramic coatings.

[0003] Fluoropolymer coatings mainly include PTFE (polytetrafluoroethylene), PFOA (perfluorooctanoic acid), PFA (a copolymer of perfluoropropyl perfluorovinyl ether and polytetrafluoroethylene), FEP (perfluoroethylene propylene copolymer), and ETFE (ethylene tetrafluoroethylene copolymer), etc. Their non-stick principle is primarily due to the extremely low surface free energy of the fluoropolymers. However, fluorinated non-stick coatings are not wear-resistant; they cannot be cleaned with metal spatulas, steel wool, or scouring pads, as they decompose at high temperatures, producing harmful substances, and their non-stick properties decrease after wear.

[0004] Ceramic coatings are primarily composed of silicon-oxygen bonds and inorganic silicon. Their non-stick principle mainly involves forming nanostructures on the surface of the pot to achieve a non-stick effect. However, ceramic coatings are less effective at preventing non-sticking than fluorinated coatings, and their non-stick properties are not as durable; the coating typically peels off after 3-6 months of use.

[0005] To address the shortcomings of both fluoropolymer coatings and ceramic coatings, an antibacterial non-stick material has been proposed, such as the antibacterial and wear-resistant composite non-stick pan coating mentioned in CN202010966414.5. This coating uses zinc and alumina powder as the base material to prepare the non-stick pan bottom layer, and adds silane-modified nano-silica sol to form a composite ceramic non-stick pan coating, aiming to obtain better non-stick properties and durable wear resistance.

[0006] However, the underlying material used in this technology has problems such as poor high-temperature resistance and low hardness, which prevents it from achieving good performance. Summary of the Invention

[0007] This invention provides a laser-coated titanium non-stick cookware, achieved through the following technical solution:

[0008] A laser-coated titanium non-stick cookware is provided, wherein a multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is prepared on the inner surface of the cookware substrate by laser thermal spraying. The multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is composed of alternating superimposed nano-composite metal-ceramic layers and nano-silicate composite ceramic layers. A superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying.

[0009] The multi-layer nano-titanium-based composite metal-ceramic coating in the aforementioned laser-coated titanium non-stick cookware is composed of a nano-composite metal-ceramic layer and a nano-silicate composite ceramic layer. The nano-composite metal-ceramic layer has good wear resistance, antibacterial properties, and high hardness, while the nano-silicate composite ceramic layer gives the non-stick, ultra-hard, high-temperature resistant coating good non-stick properties. The two layers overlap and complement each other, providing the multi-layer nano-titanium-based composite metal-ceramic coating with excellent non-stick properties, ultra-high hardness, and wear resistance, giving the cookware coated with this coating the advantage of "unrestricted stir-frying".

[0010] In some embodiments, the thickness of the nanocomposite metal-ceramic layer is 5 μm to 50 μm, the thickness of the nanosilicate composite ceramic layer is 1 μm to 6 μm, and the thickness ratio of the nanocomposite metal-ceramic layer to the nanosilicate composite ceramic layer is 2:1 to 8:1.

[0011] In some embodiments, the materials used to prepare the nanocomposite metal-ceramic coating include: 51–75.7 wt% Ti, with the balance being auxiliary components, including: 2–5 wt% TiN, 5–15 wt% TiC, 5–10 wt% SiC, 2–5 wt% TiCN, 2–5 wt% TiB, 3–10 wt% A₂O₃, 3–10 wt% ZrO, 1–10 wt% MgO, 0.1–2 wt% La₂O₃, 0–2 wt% SrO, 0.1–2 wt% Y₂O₃, and 1–3 wt% Ca. 10 (PO4)6(OH)2, 0.1-2 wt% Fe.

[0012] Among the aforementioned materials, Ti, as the main component of the nano-metal ceramic coating, possesses advantages such as excellent biocompatibility, resistance to high and low temperatures, resistance to strong acids and alkalis, and high strength. TiN, TiC, TiCN, TiB, and A2O3 exhibit superior properties such as high hardness, wear resistance, and corrosion resistance; SiC, ZrO, and MgO can reduce crack sensitivity, enhance the distribution of carbide particles, and increase the microhardness of the coating. La2O3, SrO, and Y2O3 rare earth oxides improve the uniformity of the coating and refine the microstructure. Ca... 10 (PO4)6(OH)2 has excellent biocompatibility and biological activity, and supplements the calcium element. However, calcium... 10 (PO4)6(OH)2 has poor fracture toughness, therefore its content needs to be strictly controlled. Fe can be used as a low-melting-point metal and can supplement iron.

[0013] In some embodiments, the materials used to prepare the nano-silicate composite ceramic layer include: 10-30 wt% silica sol, 10-30 wt% polymethylsiloxane, 3-10 wt% micron-sized silicon nitride, 10-20 wt% nano-sized titanium dioxide, 3-8 wt% micron-sized silicon carbide, 3-8 wt% micron-sized silicon oxide, 3-8 wt% micron-sized alumina, 5-15 wt% nano-titanium powder, 3-6 wt% wetting and dispersing agent, 2-4 wt% thickener, 5-25 wt% deionized water, 0.1-3 wt% hydroxyl silicone oil, and 1-5 wt% low-melting-point glass powder, wherein the melting point of the low-melting-point glass powder is 380-450°C, and the solid content of the silica sol is 16-20%.

[0014] In some embodiments, the materials used to prepare the nano-silicate composite ceramic layer include: 20.5 wt% silica sol, 15 wt% polymethylsiloxane, 7 wt% micron-sized silicon nitride, 13 wt% nano-sized titanium dioxide, 5 wt% micron-sized silicon carbide, 5 wt% micron-sized silicon oxide, 5 wt% micron-sized alumina, 10 wt% nano-titanium powder, 3 wt% wetting and dispersing agent, 3 wt% thickener, 10 wt% deionized water, 1.5 wt% hydroxyl silicone oil, and 2 wt% low-melting-point glass powder.

[0015] In some embodiments, the materials used to prepare the superconducting composite iron-based metal coating include: 57-82 wt% Fe, 5-15 wt% Co, 10-20 wt% Ni, and 3-8 wt% graphene.

[0016] This invention also discloses a method for preparing the multi-component, multi-layer nano-titanium-based composite metal-ceramic coating in the aforementioned laser-coated titanium non-stick cookware, wherein the nano-composite metal-ceramic coating is prepared using the following laser thermal spraying method:

[0017] (1) A nano-composite metal-ceramic powder material was sprayed onto the inner surface of a dry and clean cookware substrate using laser thermal spraying. The laser thermal spraying process parameters were: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon flow rate 20-30L / min, and powder feeding rate 8g / min.

[0018] (2) After natural cooling for 15-20 seconds, a laser thermal spray coating is formed on the inner surface of the cookware substrate. The surface of the laser thermal spray coating formed in step (1) is cleaned by blowing with argon gas at a pressure of 1-2 MPa, and then laser remelting is performed. The laser remelting process parameters are: power of 100-250W, scanning speed of 10-12mm / s, spot diameter of 4-6mm, and argon gas flow rate of 20-30L / min.

[0019] In some embodiments, the nano-silicate composite ceramic coating is prepared using the following laser thermal spraying method:

[0020] (3) After the laser remelting treatment, clean the surface with argon gas at a pressure of 1.0-2.0 MPa within 20-30 seconds, spray the nano-silicate composite ceramic coating liquid, adjust the distance between the spray gun and the substrate surface to 15-30 cm, and ensure that the nano-silicate composite ceramic coating covers the entire nano-composite metal ceramic coating. Then, use the residual heat to cure the nano-silicate composite ceramic coating.

[0021] In some embodiments, steps (1)-(3) are considered as one cycle, and the nanocomposite metal ceramic layer and the nanosilicate composite ceramic coating are alternately processed on the inner surface of the cookware substrate through 2-20 cycles to prepare the multi-element multilayer nano-titanium-based composite metal ceramic coating. The time interval between steps (1) and (2) is 10-20 seconds, the time interval between steps (2) and (3) is 20-30 seconds, and the time interval between steps (3) and (1) is 30-50 seconds.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention provides a laser titanium non-stick cookware, which provides an ultra-hard, high-temperature resistant, and long-lasting non-stick coating by means of multiple layers of nano-composite metal ceramic layer and nano-silicate composite ceramic layer stacked alternately. This coating endows the cookware with excellent non-stick properties, ultra-high hardness and wear resistance. Attached Figure Description

[0024] Figure 1 This is a graph showing the hardness test results of the laser-coated titanium non-stick cookware of Embodiment 1 of the present invention. Detailed Implementation

[0025] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0027] Unless otherwise specified, all materials used in the following embodiments are commercially available; and all methods used in the following embodiments are conventional methods unless otherwise specified.

[0028] Example 1

[0029] A laser-coated titanium non-stick cookware is provided, wherein a multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is prepared on the inner surface of the cookware substrate by laser thermal spraying. The multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is composed of alternating superimposed nano-composite metal-ceramic layers and nano-silicate composite ceramic layers. A superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying.

[0030] In this embodiment, the thickness of one layer of the nanocomposite metal-ceramic layer is 15 μm, the thickness of one layer of the nanosilicate composite ceramic layer is 5 μm, and the thickness ratio of one layer of the nanocomposite metal-ceramic layer to one layer of the nanosilicate composite ceramic layer is 3:1.

[0031] Specifically, the materials used to prepare the aforementioned nanocomposite metal-ceramic coating include: 60 wt% Ti, with the remainder being auxiliary components, namely: 3 wt% TiN, 10 wt% TiC, 6 wt% SiC, 2 wt% TiCN, 3 wt% TiB, 5 wt% A₂O₃, 6 wt% ZrO, 1.8 wt% MgO, 0.5 wt% La₂O₃, 0.2 wt% SrO, 0.5 wt% Y₂O₃, and 1 wt% Ca. 10 (PO4)6(OH)2, 1 wt% Fe.

[0032] The materials used to prepare the above-mentioned nano-silicate composite ceramic layer include: 20.5 wt% silica sol, 15 wt% polymethylsiloxane, 7 wt% micron-sized silicon nitride, 13 wt% nano-sized titanium dioxide, 5 wt% micron-sized silicon carbide, 5 wt% micron-sized silicon oxide, 5 wt% micron-sized alumina, 10 wt% nano-titanium powder, 3 wt% wetting and dispersing agent, 3 wt% thickener, 10 wt% deionized water, 1.5 wt% hydroxyl silicone oil, and 2 wt% low-melting-point glass powder. The melting point of the low-melting-point glass powder is 380-450℃, and the solid content of the silica sol is 16-20%. The materials used to prepare the above-mentioned superconducting composite iron-based metal coating include: 50-90 wt% Fe, 5-15 wt% Co, 10-20 wt% Ni, and 3-8 wt% graphene.

[0033] In this embodiment, the implementation steps and parameters of the multi-element multilayer nano-titanium-based composite metal-ceramic coating are as follows:

[0034] (1) A nano-composite metal-ceramic powder material was sprayed onto the inner surface of a dry and clean cookware substrate using laser thermal spraying. The laser thermal spraying process parameters were: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon flow rate 20-30L / min, and powder feeding rate 8g / min.

[0035] (2) After natural cooling for 15-20 seconds, a laser thermal spray coating is formed on the inner surface of the cookware substrate. The surface of the laser thermal spray coating formed in step (1) is cleaned by blowing with argon gas at a pressure of 1-2 MPa, and then laser remelting is performed. The laser remelting process parameters are: power of 100-250W, scanning speed of 10-12mm / s, spot diameter of 4-6mm, and argon gas flow rate of 20-30L / min.

[0036] (3) After the laser remelting treatment, clean the surface with argon gas at a pressure of 1.0-2.0 MPa within 10 seconds, spray the nano-silicate composite ceramic coating liquid, adjust the distance between the spray gun and the substrate surface to 15-30 cm, and ensure that the nano-silicate composite ceramic coating covers the entire nano-composite metal ceramic coating. Then, use the residual heat to cure the nano-silicate composite ceramic coating.

[0037] Furthermore, the nanocomposite metal ceramic layer and the nanosilicate composite ceramic coating are alternately processed on the inner surface of the cookware substrate in a manner of 2-20 cycles, in order to prepare the multi-element multilayer nano-titanium-based composite metal ceramic coating. The time interval between steps (1) and (2) is 10-20 seconds, the time interval between steps (2) and (3) is 20-30 seconds, and the time interval between steps (3) and (1) is 30-50 seconds.

[0038] In this embodiment, a laser-coated titanium non-stick cookware is provided. The overall manufacturing process is as follows: 1. Circular sheet stretching and forming, 2. Edge machining, 3. Cleaning, 4. Sandblasting, 5. Following the implementation steps and parameters in this embodiment, 6. Inner polishing, 7. Outer sanding, 8. Cold spraying to prepare a superconducting composite iron-based metal coating (prepared by conventional methods), 9. Sanding, 10. Spraying, 11. Assembly, 12. Packaging.

[0039] Example 2

[0040] A laser-coated titanium non-stick cookware is provided, wherein a multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is prepared on the inner surface of the cookware substrate by laser thermal spraying. The multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is composed of alternating superimposed nano-composite metal-ceramic layers and nano-silicate composite ceramic layers. A superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying.

[0041] In this embodiment, the thickness of one layer of the nanocomposite metal ceramic layer is 10 μm, the thickness of one layer of the nanosilicate composite ceramic layer is 2 μm, and the thickness ratio of one layer of the nanocomposite metal ceramic layer to one layer of the nanosilicate composite ceramic layer is 5:1.

[0042] Specifically, the materials used to prepare the aforementioned nanocomposite metal-ceramic coating include: 60 wt% Ti, with the remainder being auxiliary components, namely: 3 wt% TiN, 10 wt% TiC, 6 wt% SiC, 2 wt% TiCN, 3 wt% TiB, 5 wt% A₂O₃, 6 wt% ZrO, 1.8 wt% MgO, 0.5 wt% La₂O₃, 0.2 wt% SrO, 0.5 wt% Y₂O₃, and 1 wt% Ca. 10 (PO4)6(OH)2, 1 wt% Fe.

[0043] The materials used to prepare the above-mentioned nano-silicate composite ceramic layer include: 20.5 wt% silica sol, 15 wt% polymethylsiloxane, 7 wt% micron-sized silicon nitride, 13 wt% nano-sized titanium dioxide, 5 wt% micron-sized silicon carbide, 5 wt% micron-sized silicon oxide, 5 wt% micron-sized alumina, 10 wt% nano-titanium powder, 3 wt% wetting and dispersing agent, 3 wt% thickener, 10 wt% deionized water, 1.5 wt% hydroxyl silicone oil, and 2 wt% low-melting-point glass powder. The melting point of the low-melting-point glass powder is 380-450℃, and the solid content of the silica sol is 16-20%. The materials used to prepare the above-mentioned superconducting composite iron-based metal coating include: 50-90 wt% Fe, 5-15 wt% Co, 10-20 wt% Ni, and 3-8 wt% graphene.

[0044] In this embodiment, the implementation steps and parameters of the multi-element multilayer nano-titanium-based composite metal-ceramic coating are as follows:

[0045] (1) A nano-composite metal-ceramic powder material was sprayed onto the inner surface of a dry and clean cookware substrate using laser thermal spraying. The laser thermal spraying process parameters were: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon flow rate 20-30L / min, and powder feeding rate 8g / min.

[0046] (2) After natural cooling for 15-20 seconds, a laser thermal spray coating is formed on the inner surface of the cookware substrate. The surface of the laser thermal spray coating formed in step (1) is cleaned by blowing with argon gas at a pressure of 1-2 MPa, and then laser remelting is performed. The laser remelting process parameters are: power of 100-250W, scanning speed of 10-12mm / s, spot diameter of 4-6mm, and argon gas flow rate of 20-30L / min.

[0047] (3) After the laser remelting treatment, clean the surface with argon gas at a pressure of 1.0-2.0 MPa within 10 seconds, spray the nano-silicate composite ceramic coating liquid, adjust the distance between the spray gun and the substrate surface to 15-30 cm, and ensure that the nano-silicate composite ceramic coating covers the entire nano-composite metal ceramic coating. Then, use the residual heat to cure the nano-silicate composite ceramic coating.

[0048] Furthermore, taking steps (1)-(3) as one cycle, the nanocomposite metal ceramic layer and the nanosilicate composite ceramic coating are alternately processed on the inner surface of the cookware substrate through 2-20 cycles to prepare the multi-element multilayer nano-titanium-based composite metal ceramic coating. The time interval between steps (1) and (2) is 10-20 seconds, the time interval between steps (2) and (3) is 20-30 seconds, and the time interval between steps (3) and (1) is 30-50 seconds.

[0049] In this embodiment, a laser-coated titanium non-stick cookware is provided. The overall manufacturing process is as follows: 1. Circular sheet stretching and forming, 2. Edge machining, 3. Cleaning, 4. Sandblasting, 5. Following the implementation steps and parameters in this embodiment, 6. Inner polishing, 7. Outer sanding, 8. Cold spraying to prepare a superconducting composite iron-based metal coating (prepared by conventional methods), 9. Sanding, 10. Spraying, 11. Assembly, 12. Packaging.

[0050] Example 3

[0051] A laser-coated titanium non-stick cookware is provided, wherein a multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is prepared on the inner surface of the cookware substrate by laser thermal spraying. The multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is composed of alternating superimposed nano-composite metal-ceramic layers and nano-silicate composite ceramic layers. A superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying.

[0052] In this embodiment, the thickness of one layer of the nanocomposite metal ceramic layer is 45 μm, the thickness of one layer of the nanosilicate composite ceramic layer is 5 μm, and the thickness ratio of one layer of the nanocomposite metal ceramic layer to one layer of the nanosilicate composite ceramic layer is 8:1.

[0053] Specifically, the materials used to prepare the aforementioned nanocomposite metal-ceramic coating include: 60 wt% Ti, with the remainder being auxiliary components, namely: 3 wt% TiN, 10 wt% TiC, 6 wt% SiC, 2 wt% TiCN, 3 wt% TiB, 5 wt% A₂O₃, 6 wt% ZrO, 1.8 wt% MgO, 0.5 wt% La₂O₃, 0.2 wt% SrO, 0.5 wt% Y₂O₃, and 1 wt% Ca. 10(PO4)6(OH)2, 1 wt% Fe.

[0054] The materials used to prepare the above-mentioned nano-silicate composite ceramic layer include: 20.5 wt% silica sol, 15 wt% polymethylsiloxane, 7 wt% micron-sized silicon nitride, 13 wt% nano-sized titanium dioxide, 5 wt% micron-sized silicon carbide, 5 wt% micron-sized silicon oxide, 5 wt% micron-sized alumina, 10 wt% nano-titanium powder, 3 wt% wetting and dispersing agent, 3 wt% thickener, 10 wt% deionized water, 1.5 wt% hydroxyl silicone oil, and 2 wt% low-melting-point glass powder. The melting point of the low-melting-point glass powder is 380-450℃, and the solid content of the silica sol is 16-20%. The materials used to prepare the above-mentioned superconducting composite iron-based metal coating include: 50-90 wt% Fe, 5-15 wt% Co, 10-20 wt% Ni, and 3-8 wt% graphene.

[0055] In this embodiment, the implementation steps and parameters of the multi-element multilayer nano-titanium-based composite metal-ceramic coating are as follows:

[0056] (1) A nano-composite metal-ceramic powder material was sprayed onto the inner surface of a dry and clean cookware substrate using laser thermal spraying. The laser thermal spraying process parameters were: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon flow rate 20-30L / min, and powder feeding rate 8g / min.

[0057] (2) After natural cooling for 15-20 seconds, a laser thermal spray coating is formed on the inner surface of the cookware substrate. The surface of the laser thermal spray coating formed in step (1) is cleaned by blowing with argon gas at a pressure of 1-2 MPa, and then laser remelting is performed. The laser remelting process parameters are: power of 100-250W, scanning speed of 10-12mm / s, spot diameter of 4-6mm, and argon gas flow rate of 20-30L / min.

[0058] (3) After the laser remelting treatment, clean the surface with argon gas at a pressure of 1.0-2.0 MPa within 10 seconds, spray the nano-silicate composite ceramic coating liquid, adjust the distance between the spray gun and the substrate surface to 15-30 cm, and ensure that the nano-silicate composite ceramic coating covers the entire nano-composite metal ceramic coating. Then, use the residual heat to cure the nano-silicate composite ceramic coating.

[0059] Furthermore, taking steps (1)-(3) as one cycle, the nanocomposite metal ceramic layer and the nanosilicate composite ceramic coating are alternately processed on the inner surface of the cookware substrate through 2-20 cycles to prepare the multi-element multilayer nano-titanium-based composite metal ceramic coating. The time interval between steps (1) and (2) is 10-20 seconds, the time interval between steps (2) and (3) is 20-30 seconds, and the time interval between steps (3) and (1) is 30-50 seconds.

[0060] In this embodiment, a laser-coated titanium non-stick cookware is provided. The overall manufacturing process is as follows: 1. Circular sheet stretching and forming, 2. Edge machining, 3. Cleaning, 4. Sandblasting, 5. Following the implementation steps and parameters in this embodiment, 6. Inner polishing, 7. Outer sanding, 8. Cold spraying to prepare a superconducting composite iron-based metal coating (prepared by conventional methods), 9. Sanding, 10. Spraying, 11. Assembly, 12. Packaging.

[0061] Comparison of proportions

[0062] Comparative Example 1

[0063] Compared with non-stick cookware containing a nano-composite metal-ceramic layer (i.e., cookware described in Examples 1, 2, and 3), non-stick cookware without a nano-composite metal-ceramic layer showed a significant decrease in hardness, wear resistance, and high-temperature resistance.

[0064] Comparative Example 2

[0065] Compared with non-stick cookware containing nano-silicate composite ceramic coating (i.e., cookware described in Examples 1, 2, and 3), non-stick cookware without nano-silicate composite ceramic coating is prone to non-stick failure.

[0066] Comparative Example 3

[0067] Compared with non-stick cookware that uses argon gas cleaning during the preparation process (i.e., the cookware described in Examples 1, 2, and 3), non-stick cookware that does not use argon gas cleaning during the preparation process has unmelted particles remaining in its cladding layer, and the entire coating exhibits blistering and peeling.

[0068] For the above comparative examples, the detailed performance tests are as follows:

[0069]

[0070]

[0071] 1. Testing Item: Hardness Test

[0072] Reference standard: National Standard GB / T40737-2021

[0073] Test method:

[0074] 1) The test procedure shall be in accordance with GB / T40737-2021.

[0075] 2) Three to five test areas should be selected evenly on the same sample to measure the hardness of different areas of the cladding layer. At least three points should be tested in each area. The test results should be taken as the arithmetic mean, and the decimal should be rounded to the nearest integer. The hardness of the substrate and the heat-affected zone can be measured simultaneously.

[0076] 3) For samples that cannot be moved, sampled, or clamped, measure them according to GB / T40737-2021, convert the hardness value, and indicate this in the report.

[0077] Acceptance standard: Hardness requirement ≥650HV

[0078] 2. Test Item: Physical Non-stick Fried Egg Test

[0079] Reference standards: GB / T32095.2-2015 and Q / MST004-2020 testing standards

[0080] Test method: Heat the sample surface to 140℃~150℃, place the cracked egg on the sample surface, and continue heating to 170℃~190℃. After the egg white is basically solidified, use a plastic spatula to flip the egg. Repeat the above steps for a total of 5 cycles and record the non-stick condition of the egg.

[0081] Acceptable standard: The egg can be flipped over with a plastic spatula, and slight residue is allowed, but it can be removed by wiping with a damp sponge or cloth. All 5 cycles must be completed.

[0082] 3. Testing Item: Abrasion Resistance Test

[0083] Reference standards: GB / T32095.2-2015 and Q / MST004-2020 control and testing standards

[0084] Test method: Add 0.5% detergent solution to the sample, apply 3kg of weight with a 3M 7447B scouring pad, wet abrasion 50,000 times, and replace the scouring pad every 1,000 times.

[0085] Acceptance criteria: After testing, the exposed substrate on the coating surface must not have more than 10 linear friction marks or an area the size of a 5-cent coin.

[0086] 4. Testing items: Bottom-tapping and thermal shock tests

[0087] Reference Standard: Enterprise Testing Standard Q / MST004-2020

[0088] Test methods: The bottom of the processed cookware is slapped with hydraulic pressure to deform it. Blue oil-based ink is then applied to the inner surface coating. If cracks appear, blue cracks will be visible. The thermal shock method involves placing the cookware in an oven at around 500 degrees Celsius for 5 minutes. After that, it is removed and quickly cooled in room temperature water. No cracks were observed after 10 cycles.

[0089] Acceptable criteria: No cracks, no blistering, and no peeling.

[0090] 5. Testing Item: Adhesion

[0091] Reference standard: National Standard GB / T2421-1998

[0092] Test method: Use a sharp knife to make 11 parallel scratches 2.4 mm apart and 38 mm long on the coating. Make more than 100 scratches in a vertical direction. Stick transparent tape (3M-898) on the scratches, press it flat or stick it firmly with your fingers, hold the other end with your fingers and pull it up quickly at a 90-degree right angle. Repeat 3 times.

[0093] Acceptance criteria: No coating peeling.

[0094] The above detailed description is a specific description of feasible embodiments of the present invention. These embodiments are not intended to limit the scope of protection of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of protection of the present invention.

Claims

1. A laser-coated titanium non-stick cookware, characterized in that: A multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is prepared on the inner surface of the cookware substrate by laser thermal spraying. The multi-element, multi-layer nano-titanium-based composite metal-ceramic coating is composed of alternating superposition of nano-composite metal-ceramic layers and nano-silicate composite ceramic layers. A superconducting composite iron-based metal coating is prepared on the outer side of the bottom of the cookware by cold spraying. The materials used to prepare the nanocomposite metal-ceramic coating include: 51-75.7 wt% Ti, with the balance being auxiliary components, which include: 2-5 wt% TiN, 5-15 wt% TiC, 5-10 wt% SiC, 2-5 wt% TiCN, 2-5 wt% TiB, 3-10 wt% A₂O₃, 3-10 wt% ZrO, 1-10 wt% MgO, 0.1-2 wt% La₂O₃, 0-2 wt% SrO, 0.1-2 wt% Y₂O₃, and 1-3 wt% Ca. 10 (PO4)6(OH)2, 0.1-2wt% Fe; The materials used to prepare the nano-silicate composite ceramic layer include: 10-30 wt% silica sol, 10-30 wt% polymethylsiloxane, 3-10 wt% micron-sized silicon nitride, 10-20 wt% nano-sized titanium dioxide, 3-8 wt% micron-sized silicon carbide, 3-8 wt% micron-sized silicon oxide, 3-8 wt% micron-sized alumina, 5-15 wt% nano-titanium powder, 3-6 wt% wetting and dispersing agent, 2-4 wt% thickener, 5-25 wt% deionized water, 0.1-3 wt% hydroxyl silicone oil, and 1-5 wt% low-melting-point glass powder; the melting point of the low-melting-point glass powder is 380-450℃, and the solid content of the silica sol is 16-20%.

2. The laser-coated titanium non-stick cookware according to claim 1, characterized in that: The thickness of the nanocomposite metal-ceramic layer is 5μm~50μm, the thickness of the nanosilicate composite ceramic layer is 1μm~6μm, and the thickness ratio of the nanocomposite metal-ceramic layer to the nanosilicate composite ceramic layer is 2:1~8:

1.

3. The laser-coated titanium non-stick cookware according to claim 1, characterized in that: The materials used to prepare the nanocomposite metal-ceramic coating include: 60 wt% Ti, with the balance being auxiliary components, namely: 3 wt% TiN, 10 wt% TiC, 6 wt% SiC, 2 wt% TiCN, 3 wt% TiB, 5 wt% A₂O₃, 6 wt% ZrO, 1.8 wt% MgO, 0.5 wt% La₂O₃, 0.2 wt% SrO, 0.5 wt% Y₂O₃, and 1 wt% Ca. 10 (PO4)6(OH)2, 1wt% Fe.

4. The laser-coated titanium non-stick cookware according to claim 1, characterized in that: The materials used to prepare the nano-silicate composite ceramic layer include: 20.5 wt% silica sol, 15 wt% polymethylsiloxane, 7 wt% micron-sized silicon nitride, 13 wt% nano-sized titanium dioxide, 5 wt% micron-sized silicon carbide, 5 wt% micron-sized silicon oxide, 5 wt% micron-sized alumina, 10 wt% nano-titanium powder, 3 wt% wetting and dispersing agent, 3 wt% thickener, 10 wt% deionized water, 1.5 wt% hydroxyl silicone oil, and 2 wt% low-melting-point glass powder.

5. The laser-coated titanium non-stick cookware according to claim 1, characterized in that: The materials used to prepare the superconducting composite iron-based metal coating include: 57-82 wt% Fe, 5-15 wt% Co, 10-20 wt% Ni, and 3-8 wt% graphene.

6. The method for preparing the multi-element, multi-layer nano-titanium-based composite metal-ceramic coating in the laser-coated titanium non-stick cookware according to any one of claims 1-5, characterized in that, The nanocomposite metal-ceramic coating was prepared using the following laser thermal spraying method: (1) A nano-composite metal-ceramic powder material was sprayed onto the inner surface of a dry and clean cookware substrate using laser thermal spraying. The laser thermal spraying process parameters were: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon flow rate 20-30L / min, and powder feeding rate 8g / min. (2) After natural cooling for 15-20 seconds, a laser thermal spray coating is formed on the inner surface of the cookware substrate. The surface of the laser thermal spray coating formed in step (1) is cleaned by blowing with argon gas at a pressure of 1-2 MPa, and then laser remelting is performed. The laser remelting process parameters are: power of 100-250W, scanning speed of 10-12mm / s, spot diameter of 4-6mm, and argon gas flow rate of 20-30L / min.

7. The preparation method according to claim 6, characterized in that, The nano-silicate composite ceramic coating was prepared using the following laser thermal spraying method: (3) After the laser remelting treatment, clean the surface with argon gas at a pressure of 1.0-2.0 MPa within 20-30 seconds, spray the nano-silicate composite ceramic coating liquid, adjust the distance between the spray gun and the substrate surface to 15-30 cm, and ensure that the nano-silicate composite ceramic coating covers the entire nano-composite metal ceramic coating. Then, use the residual heat to cure the nano-silicate composite ceramic coating.

8. The preparation method according to claim 7, characterized in that: The nanocomposite metal ceramic layer and the nanosilicate composite ceramic coating are alternately processed on the inner surface of the cookware substrate in a manner of 2 to 20 cycles, with each step (1), (2), and (3) forming a cycle. The time interval between steps (1) and (2) is 10-20 seconds, the time interval between steps (2) and (3) is 20-30 seconds, and the time interval between steps (3) and (1) is 30-50 seconds.

Citation Information

Patent Citations

  • An antibacterial and wear-resistant composite non-stick cookware coating and its preparation method

    CN112080204B

  • Laser cladding non-stick pan and manufacturing method thereof

    CN112220331A